Targeting β-Catenin Signaling by Natural Products for Cancer Prevention and Therapy - Yu, Wen-Kai; Xu, Zhi-Yuan; Yuan, Li; Mo, Shaowei; Xu, Beihua; Cheng, Xiang-Dong; Qin, Jiang-Jiang (Frontiers in Pharmacology, 2020)
The mutations and deregulation of Wnt signaling pathway occur commonly in human cancer and cause the aberrant activation of β-catenin and β-catenin-dependent transcription, thus contributing to cancer development and progression. Therefore, β-catenin has been demonstrated as a promising target for cancer prevention and therapy. Many natural products have been characterized as inhibitors of the β-catenin signaling through down-regulating β-catenin expression, modulating its phosphorylation, promoting its ubiquitination and proteasomal degradation, inhibiting its nuclear translocation, or other molecular mechanisms. These natural product inhibitors have shown preventive and therapeutic efficacy in various cancer models in vitro and in vivo. In the present review, we comprehensively discuss the natural product β-catenin inhibitors, their in vitro and in vivo anticancer activities, and underlying molecular mechanisms. We also discuss the current β-catenin-targeting strategies and other potential strategies that may be examined for identifying new β-catenin inhibitors as cancer preventive and therapeutic drugs.